Effects of Green Tea (Camellia Sinensis) on Liver Histology of Mice on High Fat Diet (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To evaluate the effects of green tea on liver histology of mice on high fat diet. Study Design: Analytical experimental randomized control trial. Place & Duration of Study: Department of Anatomy, Army Medical College, Rawalpindi and National Institute of Health, Islamabad. Twelve weeks from May 2009 - July 2009. Material & Methods: Sixty adult mice, Balb-C strain were selected and divided into three groups. The control group was given standard laboratory diet throughout the study. In experimental group A, the study was carried out in two phases. In the first phase, hepatic steatosis was induced by high fat diet containing 4 percent cholesterol powder and 40 percent butter fat for six weeks. In the second phase, experimental group was given normal diet with 1 percent green tea over a period of next six weeks. The experimental group B was given high fat diet containing 4 percent cholesterol powder and 40 percent butter fat with 1 percent green tea over a period of twelve weeks. Ten mice in each were sacrificed at six weeks & remaining ten were sacrificed at twelve weeks. Results: Showed that high fat diet for six weeks produced significant hepatic steatosis, evident on histological analysis. When experimental group A (induction phase) with high fat diet was compared with the (reversal phase) on normal diet and green tea, statistically significant difference (p
Keywords: Camellia Sinensis, Histomorphology of liver.